Gambaran Kecenderungan Cinderella Complex Pada Perempuan Dalam Toxic Relationship - Nabila Ikram; Rohmah Rifani; Eka Sufartianinsih Jafar (CV. Multi Kreasi Media, 2023)
The view that women who have Cinderella complex tendencies who experience toxic relationships will find it difficult to move away or escape from unhealthy relationships because of their dependence on their partners. Based on initial observations and interviews, there are still many women who are trapped in unhealthy or toxic relationships but still survive for reasons of dependence on their partners. This study aims to determine the tendency of Cinderella complex in women in toxic relationships. Respondents inthis study amounted to 3 people. The method used in this research is a case study with a qualitative approach. Based on the results of the study, it shows that the three respondents have a picture of the Cinderella complex in the form of always expecting support and help from others. Two of the respondentsrelied heavily on their partners in facing the difficulties experienced in their lives. In addition, the three respondents both showed a lack of ability to believe in themselves. However, the differences between the three respondents in terms of the number of images seen vary between each respondent. The three respondents were equally influenced by aspects of external self-control and low self-esteem. The implications of this research are as a reference and reflection for further researchers in studying the cinderella complex in women.